2019
DOI: 10.1038/s41598-019-44858-0
|View full text |Cite
|
Sign up to set email alerts
|

Contrapositive logic suggests space radiation not having a strong impact on mortality of US astronauts and Soviet and Russian cosmonauts

Abstract: Space travelers are exposed to unique forms of ionizing radiation that pose potentially serious health hazards. Prior analyses have attempted to quantify excess mortality risk for astronauts exposed to space radiation, but low statistical power has frustrated inferences. If exposure to deep space radiation were causally linked to deaths due to two particular causes, e.g., cancer and cardiovascular disease, then those cause-specific deaths would not be statistically independent. In this case, a Kaplan-Meier sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The Guest Edited Collection ‘ Gravitational biology and space medicine ’ includes publications reporting on health concerns for astronauts and cosmonauts 1416 during space missions, and physiological changes caused by short-term µ g 17 . Several studies investigating the impact of µ g on the behaviour and health of mice on the ISS were published in this Collection 1823 , in addition to investigations at the cellular level in space 24 and in short-term µ g provided by PF maneuvers 25 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Guest Edited Collection ‘ Gravitational biology and space medicine ’ includes publications reporting on health concerns for astronauts and cosmonauts 1416 during space missions, and physiological changes caused by short-term µ g 17 . Several studies investigating the impact of µ g on the behaviour and health of mice on the ISS were published in this Collection 1823 , in addition to investigations at the cellular level in space 24 and in short-term µ g provided by PF maneuvers 25 .…”
mentioning
confidence: 99%
“…Reynolds et al . 16 , investigated 301 astronauts and 117 cosmonauts, demonstrating that space radiation has no strong impact on their mortality. They showed that survival estimates from Kaplan-Meier curves were largely congruent with those of competing risk methods, suggesting that if ionising radiation impacts the risk of death due to cancer and cardiovascular disease, the effect is not dramatic 16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In aircrew, despite a consistent finding of lower risk of CVD mortality compared to the general population, the prevalence of CAD in pilots is the same as age-matched controls in the general population, 18,19 and whilst most experienced astronauts are middle aged, and at risk for developing major adverse cardiovascular events, recent contemporary data has revealed similar rates of developing CVD as the general population despite exposure to spaceflight. [20][21][22][23] In the military, like the general population, the most frequent cause of death is CAD, with an increasing trend seen with increasing age. [24][25][26] Whilst recruiting at a younger age, a focus on physical fitness, 27,28 reduced obesity levels [29][30][31] and the early discharge of those with conditions known to predispose to CVD, such as diabetes, 29,31 chronic kidney disease or rheumatoid arthritis, may reduce the burden of CVD, 32,33 a higher proportion of males recruited from lower socioeconomic groups, increased rates of smoking 31,[34][35][36] and a paradoxical increased rate of cardiovascular events due to vigorous exertion may not only negate any benefits, but worsen cardiovascular health in comparison to the comparative normal population.…”
Section: Healthy Worker Effectmentioning
confidence: 99%
“…The database has been used extensively in prior publications concerning astronaut mortality. [5][6][7] Counts of tumors and cancer deaths were obtained from the 2019 issue of the newsletter of the Lifetime Surveillance of Astronaut Health (LSAH) at NASA, with input from the LSAH on speci c tumor and death counts. 8 In comparison to the original source table, 2 cancers (1 melanoma and 1 testicular) were removed from the tumor counts, as they were diagnosed prior to time of selection to the Astronaut Corps.…”
Section: Study Population and Datamentioning
confidence: 99%